Embodied energy analysis of building materials: An improved IO-based hybrid method using sectoral disaggregation. (1st April 2017) - Dixit, Manish K.
Abstract: Buildings consume approximately half of the annual energy supply of the United States in their construction and operation. To effectively decrease this extensive energy footprint, both embodied and operating energy must be quantified and optimized. Although validated standard methods are available to compute operating energy, quantifying embodied energy is still complicated and inconsistent. Among the available embodied energy calculation methods, an input-output-based hybrid (IOH) method has the potential to offer a more complete calculation. However, its calculation lacks specificity and reliability, which can be improved using suggestions provided by literature. Studies across the globe have proposed techniques such as sectoral disaggregation to enhance not only the specificity and reliability, but also the completeness, of an IOH method. This study investigated and improved an IOH method of embodied energy calculation. Using the improved method, the embodied energy of commonly used building materials was calculated and evaluated. The results demonstrate a significant difference after disaggregating the relevant industry sectors. The study concludes that using embodied energy values without industry sectors being disaggregated can cause significant errors in a building's embodied energy calculation. Highlights: The specificity of an IO-based hybrid method (IOH) is improved using the sectoral disaggregation process. Using the improved method, the embodied energy of 21 construction materials is computed and evaluated. Results suggest that not disaggregating industry sectors may cause errors to embodied energy calculations. Results also indicate that an IOH method can cover a wider system boundary than process-based methods.